(untitled) (Asian Journal of Plant Biology, 2014)
In this work, a novel source of protease for the bioassay of heavy metals has been developed using proteases extracted from garlic (Allium sativum). The principle of casein-Coomassie-dye binding assay has been applied for this purpose. The optimum concentration of enzyme and substrate were determined at 0.7 mg/mL and 0.175 mg/mL, respectively. The crude proteases of Allium sativum exhibited optimal activity at pH 6.0, temperature at 40oC and incubation time of 60 minutes. The IC50 values for mercury, copper, cadmium, nickel and chromium were 0.0590 mg/L, 0.6398 mg/L, 1.291 mg/L, 0.9865 mg/L and 1.871 mg/L, respectively. The calculated limits of quantitation (LOQ) value for mercury, copper, cadmium, nickel and chromium were 0.0188 mg/L, 0.025 mg/L, 0.50 mg/L, 0.10 mg/L and 0.5 mg/L, respectively. The calculated LOD values for mercury, copper, cadmium, nickel and chromium were 0.0002 mg/L, 0.006 mg/L, 0.05 mg/L, 0.02mg/L and 0.1 mg/L, respectively. The crude proteases extracted from Allium sativum showed good potential for the development of a rapid, sensitive, and economic inhibitive assay for the biomonitoring of mercury, copper, cadmium, nickel and chromium in the environments.